THE IDEOLOGY OF NATIONAL EDUCATION CELEBRATION SPEECH: A CRITICAL DISCOURSE ANALYSIS OF TEXT - Shofie Nurul Azizah; Fahry Rizaldy Putra (LPPM STBA Pontianak, 2024)
This study aims to discover critical discourse analysis in the text of speeches by Nadiem Makarim and Muhadjir Effendy. The speeches of these two figures were chosen because the text is a kind of Critical Discourse Analysis object (CDA). The Critical Discourse Analysis (CDA) method examines the relationship between language, ideology, and power. The descriptive qualitative method was used in this study. The researcher uses Norman Fairclough's three-dimensional framework (CDA) to analyze Critical Discourse Analysis data. The researchers used qualitative data analysis theory from Miles and Huberman (1994) to present and analyze the data, which included data reduction, data display or representation, and conclusion drawing or verification. The result of this study shows that both the script of speeches from Nadiem Makarim and Muhadjir Effendy have micro, mezzo, and macro-level related to the framework of Norman Fairclough. The language used in both speeches is the standard language. Still, the speech of Nadiem Makarim used more natural and creative language that can touch the millennial generations. In contrast, in the speech of Muhadjir, familiar words can confuse the audience.